The association between obesity and sedentary behavior or daily physical activity among children with Down's syndrome aged 7–12 years in Japan: A cross-sectional study. Issue 9 (September 2020) - Yamanaka, Erika; Inayama, Takayo; Ohkawara, Kazunori; Okazaki, Kanzo; Kita, Ichiro
Abstract: Background: An assessment of the adverse health effects of obesity in children with Down's syndrome (DS) is required to develop programs that facilitate the acquisition of healthy behaviors. Individuals with DS are often obese. These individuals must develop health related behaviors in childhood. For this reason, it is necessary to clarify the factors associated with obesity in children with DS. Aims: This study had two purposes. The first was to assess the obesity and to evaluate the sedentary behavior (SB) and physical activity of Japanese elementary school children with Down's syndrome. The second was to investigate the association between obesity and SB or moderate to vigorous physical activity (MVPA). Methods and procedures: Ninety-three children (male/female: 51/42) with DS in elementary school grades 1 to 6 (aged 7–12 years) participated in this study in Japan. Physical characteristics were obtained from the questionnaire completed by their parents. The questionnaire provided information on regular school checkups. SB and MVPA were evaluated using a triaxial accelerometer. Results: Approximately 20% of the children with DS were obese. Nearly half of the children with DS achieved 60 min of MVPA. SB time was significantly longer in the upper grades (aged 11–12 years) than in the lower grades (aged 7–8 years). Comparing weekdays and weekend days, the middle (aged 9–10 years) and upper grades had significantly shorter MVPA times on weekend days. The frequency of obesity was significantly associated with shorter MVPA times in the lower grades and longer SB time in the middle grades. Conclusions and implications: Children with DS may increase their SB time as their age group (grade category) increases. Increasing opportunities for MVPA during weekends may increase physical activity. The observed relationship between obesity and SB time or MVPA time may apply only to younger and middle grade children with DS. Further investigation is necessary to confirm these relationships. Abstract : Disability; Health Education; Health Sciences; Nutrition; Physical Activity; Elementary schoolchildren; Down's syndrome; accelerometer; Physical Activity; Obesity; japan.